A dinâmica espacial do transporte na consolidação da cadeia produtiva do leite no Sudoeste do Paraná - Camilo, Pablo Jonas (2013)
The production, transportation, and industrialization of milk in Paraná undergone substantial institutional, structural, and technological changes over the last decades that promoted changes in spatial dynamics occupied by the milk chain. The agro-industrial companies, for the most part, have undertaken some improvement, incorporating more effective machinery and equipment to maintain competitiveness in their production lines. The demand for greater efficiency exerted on other links in the chain, reaching producers, and transporters generated technological innovations in the processes, machinery, equipment, products and supplies, making it important objects of analysis. The adjustments made in response to the specific challenges led to dynamics to the region. Based on this analysis, this paper presents results of study on the dynamics of capitation and transportation of milk as a result of the development of the dairy industry and milk production, considering the category of socio-spatial training combined with the idea of geographical combinations and dynamic character of the development of the capitalism.